Near surface air humidity in a megadiverse Andean mountain ecosystem of southern Ecuador and its regionalization - Fries, Andreas; Rollenbeck, Rütger; Nauss, Thomas; Peters, Thorsten; Bendix, Jörg (Agricultural and Forest Meteorology, 2012)
The near surface humidity in a megadiverse mountain ecosystem in southern Ecuador is examined on the basis of Relative Humidity (RH) measurements inside the natural mountain forest and at open sites along an altitudinal gradient from 1700 to 3200 m. The main methodological aim of the current study is to generate a humidity regionalization tool to provide spatial datasets on average monthly mean, minimum and maximum RH, Specific Humidity (q) and Specific Saturation Deficit (DS) by using observation data of RH. The maps based on data of the period 1999–2009 are needed by ecological projects working on various plots where no climate station data are available. The humidity maps are generated by combining a straightforward detrending technique with a Digital Elevation Model and a satellite-based land cover classification which also provides the relative forest cover per pixel. The topical aim of the study is to investigate the humidity distribution and structure of both manifestations of our ecosystem (pastures and natural vegetation) with special considerations to the ecosystem regulation service by converting natural forest into pasture. The results reveal a clear differentiation over the year, partly triggered by the change of synoptic weather situation but also by land cover effects. Humidity amplitudes are particularly low during the main rainy season when cloudiness and rainfall are high, but markedly pronounced in the relative dry season when daily irradiance and outgoing nocturnal radiation causes distinct differences between the land cover units. Particularly the upper pasture areas gained by slash and burn of the natural forest exhibit the lowest humidity values while the humidity inside the mountain forest is significantly higher due to the regulating effects of the dense vegetation. Thus, clearing the forest clearly reduces the regulation function (regulating ecosystem services) of the ecosystem which might become problematic for reforestation under future global warming
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IG.zentr.nearsu